Far from the madding crowd - Hardy, Thomas (Penguin Books London, 2020)
"Bathsheba Everdene is young and beautiful. She has her own farm and she likes to do things her way. Three men are in love with her - a poor shepherd, a rich farmer and a soldier. Which man will she choose, and will he be the right one for her? Penguin Readers is an ELT graded reader series for learners of English as a foreign language. With carefully adapted text, new illustrations and language learning exercises, the print edition also includes instructions to access supporting material online." -- provided by publisher